EFIKASI DIRI SISWA DAN IMPLIKASINYA DALAM BELAJAR DI RUMAH BELAJAR YAYASAN CINTA BANGSA (YLBC) SUKU TA WANA, WATU BAMBANG MOROWALI UTARA, SULAWESI TENGAH - Rudy Aldri Alouw; Meidy Widiastuti Sangkianti (SAINT PAUL'S REVIEW, 2021)
This research aimed to evaluate self-efficacy of the students of Yayasan Cinta Lentera Bangsa due to lower study interest. Subject of research is 8 teenager students from Ta Wana tribe in Watu Bambang village, Mt. Takaloka, north Morowali , central Sulawesi. Methods of research used are observation, limited interviews, and House-Tree-Person projective test. From the research, we may conclude that most subjects has low self-efficacy influenced by their internal emotions, family parenting and social connection related to sexual factor.